AMERICAN ELITES EDUCATION IN THE EIGHTEENTH-CENTURY SPAIN. - Chaparro Sainz, Álvaro (Revista de Historia Social y de las Mentalidades, 2012)
The accession to the throne of Spain of the Bourbon dynasty brought with it several reforms in the administrative and political realms. As a consequence, the channels of recruitment of the men who had to serve the King were also changed. In this context of change, I think compulsory to consider the appearance of new educational institutions, such as the Seminarios de Nobles, which brought new technical and specialized advancements. The elites located in Spain took advantage of these institutions to form their descendants, but what happened with the elites located in America? Did they also send their relatives to these institutions? Did they benefit from the same channels of social reproduction that the families of the elites closer to the Court employed? In this essay, I want to find an answer to these questions and study the education of the Indian elites coming to Spainin order to discover which were their family practices within this context of change.